Probabilistic seismic hazard analysis of Nepal considering validated seismic source model - Agriya Sagar Pandit,; Joshi, Dilendra Prasad; Subedi, Chetana; Alisha Poudel,; Sharma, Roshan; Pawan Chhetri, (Journal of Engineering Issues and Solutions, 2024)
Earlier studies have performed Probabilistic Seismic Hazard Analysis (PSHA) of Nepal considering different source models. This study aims to validate the best seismic source model to perform PSHA in Nepal. Earthquake data from earthquake catalogues for the period of 1900 to 2022 AD has been considered. The earthquake data obtained from catalogues was homogenised and merged. De-clustering was performed to remove dependent events using ZMAP. A completeness test was performed and recurrence parameters were computed. As proposed in earlier studies, Peak Ground Acceleration (PGA) values were calculated for 3D source, fault source and areal sources for 6.36% probability of exceedance for 50 years. A comparison was made between the PGA values of all source models with the recorded PGA value of the Kirtipur (KTP) station for the 2015 Gorkha Earthquake for a 760-year return period. The comparison of PGA values proves the Single Ramp Model (SRM) of the Main Himalayan Thrust (MHT) to be the validated seismic source model for Nepal. PSHA was then performed with the validated source model and hazard maps were prepared for 2% and 10% probability of exceedance. The analysis revealed that PGA values reached maximum levels in the far western and central regions. Using a single ramp model of MHT with improved Ground Motion Prediction Equations (GMPEs) specific to the Himalayan region is necessary for future seismic hazard analysis.